ANALISIS TENTANG EMPLOYEE ENGAGEMENT PADA PERUSAHAAN JASA (STUDI PADA KARYAWAN PATRA JASA CONVENTION HOTEL SEMARANG) - Puspadewi, Ulfa Isnani; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2016)
This study aimed to identify the antecedents and consequences of employee engagement. Employee engagement has a strong effect on the organizational performance. Good level of employee performance and the low level of absenteeism which indicates that there is a good level of employee engagement at Patra Jasa Convention Hotel Semarang. This study held in the employees of Patra Jasa Convention Hotel Semarang. Data collected through distribution of questionnaires to 107 permanent employees with census method. The techniques of data testing in this research includes validity test by factor analysis, reliability test, the classical assumption test, multiple linear regression, path analysis, and the Sobel test to examine the mediation effect with SPSS 16.0. The results of this study indicates that job characteristics, procedural justice, and rewards and recognition have positive and significant effect to employee engagement. While, distributive justice has a positive but not significant effect to employee engagement. Employee engagementÂ  has positive and significant effect to employee performance, job satisfaction, and organizational commitment. Employee engagement is partially connects antecedents with consequences.